Microbial Production of Violacein and Process Optimization for Dyeing Polyamide Fabrics With Acquired Antimicrobial Properties - Kanelli, Maria; Mandic, Mina; Kalakona, Margarita; Vasilakos, Sozon; Kekos, Dimitris; Nikodinovic-Runic, Jasmina; Topakas, Evangelos (Frontiers in Microbiology, 2018)
In the present study, crude bacterial extract containing violacein is investigated for the preparation of antimicrobial polyamide fabrics. The optimal culture conditions for maximum biomass and violacein production were found to be 25 oC, pH 7.0, while the addition of ampicillin of 0.2 mg mL-1 in the small scale increased violacein production 1.3-fold. In scale-up trials, the addition of 1 % (v/v) glycerol in a fed batch bioreactor, resulted in 5-fold extracted crude violacein increase with final concentration of 1.828 g L-1. Polyamide 6.6 fabrics were dyed following three different processes; through simultaneous fermentation and dyeing (SFD), by incubating the fabric in the sonicated bacterial culture after fermentation and by using cell-free extract containing violacein. Maximum color change (ΔΕ) and color strength (K/S) obtained for SFD fabrics were 74.81 and 22.01, respectively, while no alteration of fastness and staining of dye at acid and alkaline perspiration or at water was indicated. The dyed fabrics presented significant antifungal activity against Candida albicans, Candida parapsilosis and Candida krusei, as well as antibacterial properties against Escherichia coli, Staphylococcus aureus and the S. aureus MRSA. We have shown that J. lividum cultures can be successfully used for violacein production and for simultaneous dying of fabrics resulting in dyed fabrics with antimicrobial properties without utilization of organic solvents.